Response to mepolizumab treatment is sustained across 4-weekly dosing periods. Issue 3 (14th September 2020) - Pavord, Ian D.; Bleecker, Eugene R.; Buhl, Roland; Chanez, Pascal; Bel, Elisabeth H.; Howarth, Peter; Bratton, Daniel J.; Albers, Frank C.; Yancey, Steven
Background: Mepolizumab (100 mg delivered s.c. every 4 weeks) is indicated for add-on maintenance treatment for patients with severe eosinophilic asthma. Mepolizumab has been shown to reduce exacerbations and the requirement for daily oral corticosteroids, and improve asthma control and symptoms. However, data on the durability of the response to mepolizumab during dosing periods are limited. The aim of this study was to investigate the efficacy profile in patients with severe eosinophilic asthma over the 4-weekly dosing period for various fixed mepolizumab doses. Methods: This was a post hoc analysis of data from the phase IIb/III DREAM study. Patients ≥12 years of age with severe eosinophilic asthma were randomised (1:1:1:1) to receive intravenous mepolizumab 75 mg (equivalent to 100 mg s.c.), 250 mg, 750 mg or placebo, plus standard of care, every 4 weeks for 52 weeks. The number of exacerbations and eDiary data (peak expiratory flow, rescue medication use and symptom scores) from two periods in each 4-weekly dosing interval (days 1–14 and 15–28) over the 52-week treatment period were analysed. Findings: eDiary data and the proportion of patients experiencing ≥1 exacerbation were similar during the first and second 2 weeks of a dosing period across all mepolizumab doses. Interpretation: These results demonstrate that the response to mepolizumab is sustained over the 4-weekly dosing period with no differences across a 10-fold dose range and supports the use of the current mepolizumab dosing regimen in patients with severe eosinophilic asthma. Post hoc analysis of data from DREAM demonstrated a sustained response to mepolizumab across the 4-weekly dosing period, suggesting therapeutic benefit is maintained between each mepolizumab dose following long-term treatment https://bit.ly/3843lH6